Coming up for air - Daley, Tom, 1994- (Hanover Square Press, 2022)
"In this deeply personal memoir, the celebrated Olympic Gold Medal diver and LGBTQ+ advocate discusses his struggles, triumphs and how he developed the mindset to compete at an elite level."